5S Culture of Excellence in Facilities and Infrastructure Management in Higher Education Institutions - Cahya Kirani; Rohmatun Lukluk Isnaini; Agil Amirus Sholichin; Ahmad Naufal Gumilang; Fitrianingsih (Didaktika: Jurnal Kependidikan, 2023)
The 5S management method (seiri, seiton, seiso, sheiketsu, shitsuke) that manufacturing companies originally applied was adapted and applied in educational institutions. The process of internalization from the industrial sector towards education, such as higher education institutions, certainly requires modifications and encounters different challenges and solutions. Therefore, this study aims to discover the concept of a superior culture of 5S in managing facilities and infrastructure in higher education institutions. This study uses a systematic literature review method through the identification, evaluation, and interpretation stages of Kitchenham. Several publishers, such as Science Direct, Emerald Insight, Research Gate, Google Scholar, and Garuda, have reviewed the articles published in the last ten years. In addition, several articles and other literature were also included as reference material to strengthen the research results. The results show that 1) the 5S concept can be applied in higher education institutions with certain adjustments based on needs and abilities; 2) challenges in 5S Implementation include the role of leadership and shared commitment. The strategy to achieve it requires the Plan, Do, and Check stages. So, it can be concluded that 5S can be applied as a work culture in managing facilities and infrastructure in higher education institutions.